WORD COLLECT: WORD GAMES AS LANGUAGE TEACHING MEDIA IN LEARNING VOCABULARY - Rosniar, Rosniar (Lembaga Jurnal FKIP Universitas Bosowa, 2022)
The objectives of the research were to know whether the implementation of Word Collect: Word Games as Language Teaching Media effective in Learning Vocabulary. The writer was applied pre-experimental with one group pre-test and post-test. This research was conducted at UPT SPF SMP Negeri 36 Bulukumba. In this research, the population was the seven grade students of UPT SPF SMP Negeri 36 Bulukumba in academic year 2021/2022. The total numbers of population were 140 students. The researcher was used total sampling technique. The total number of samples was 12 students from class IX. In analyzing the numerical data, the writer used SPSS for windows. After conducted the research, the writer concludes that that the use of Word Collect: Word Games in teaching English vocabulary enriches the students’ vocabulary; it is proved by the mean score of the students in pre-test and posttest. The mean score of the pre-test before the treatment was 61.30 and after the treatment the students gained score 75.17. The t-test of the students’ vocabulary achievement in posttest was smaller than α. The researcher found that the p-value (probability value) was lower than α (0.00 < 0.05) and the degree of freedom was 11. The t-test value of pre-test and post-test was remarked significantly different. It indicated that the alternative hypothesis (H1) was accepted and, of course, the null hypothesis (H0) was rejected